Current Challenges in Teaching English in Least-developed Region in Indonesia - Antonius Setyawan Nur Agung (Soshum: Jurnal Sosial dan Humaniora, 2019)
Teaching English as a Foreign Language is challenging. The body of literature has addressed the issue on the current challenges in teaching English as Foreign Language. However, only few studies have investigated the issue in remote areas of Indonesia. This qualitative study investigates the current challenges in teaching English in least-developed region of Indonesia based on the following criteria: language comprehension, method and approach, practical implementation, and socio-cultural environment. The data were collected from four English lecturers in one of teaching universities in Indonesia. The participants were selected using purposive sampling technique. The data were collected using in-depth interview and field observation which were then analyzed descriptively. The results of the study reveal that the participants have to deal with several obstacles in teaching English. Those obstacles include the students’ low proficiency of language comprehension, limited resources of materials, communication gap between lecturers and students, students’ lack of enthusiasm and participation in learning and lack of environmental support from society. From the observation, the participants show that the challenges are mitigated by adjusting their choice of pedagogical instruction and learning materials according to students’ level of language comprehension. The study suggests that the infrastructure development is strongly essential to establish a good teaching environment. Besides, creating positive understanding and paradigm about the sanctity of learning English for students might be able to help the students’ to study English better.